The equation of acoustic rays in an inhomogeneous moving medium - MAKAREWICZ, Rufin (Archives of Acoustics, 1976)
This paper is devoted to the derivation of the differential equations for rays in an inhomogeneous medium which moves with a velocity W(z). The velocity of sound propagation in this medium is assumed to be a function of one variable a(z). The discussion is based on the Snell’s generalized law which has been derived by a new method.